ANALISIS WACANA KRITIS PADA TAJUK (ANTI) KORUPSI DI SURAT KABAR BERBAHASA INDONESIA - MArdikantoro, Hari Bakti (LITERA, 2014)
This study aims to describe newspaper attitudes towards and views of corruption cases in Indonesia, manifested in (anti-)corruption editorials. Newspaper attitudes are manifested through two frames, namely the one criticizing corruption news and the other supporting corruption news. The data were collected through a literature review and a recording method. They were analyzed by the correspondence and participatory methods. The findings are as follows. First, by criticizing corruption news, Koran Tempo in its two editorials indicates a disagreement over corruption news. The disagreement is caused by several weird facts in the court and the defense for the corruption investigator who, quite the contrary, was sent to prison. Second, with a frame of supporting corruption news, Kompas, Republika, Koran Tempo, Jawa Pos, and Suara Merdeka have attitudes and views indicating agreement to support corruption news in newspapers. The support refers to efforts to eradicate corruption that can be manifested in the arrest of a suspect in corruption, the court, and the verdict on a suspect in corruption.